INVESTIGATION OF TUNNEL RESPONSE DUE TO THE EFFECT OF ADJACENT LOADED PILE ROW BY 3D SIMULATION ANALYSIS - Narunat Heama (My University, 2022)
The construction of tunnels for transportation, wastewater, electricity, etc., in the major cities has flourished.In the meantime, other infrastructures such as elevated trains, and flyovers, are continually constructed for urbanization.Under a soft ground condition, they are supported by the pile foundations required pile rows which are possibly located along the existing tunnel.A common challenge encountered in the loaded pile row of the new adjacent structures is inevitably inducing soil stress changes and deformation of existing tunnels.Thus, an assessment of the impact of pile underloading on the integrity of the existing tunnels is essential.The three-dimensional finite element analyses (3D FEA) with two pile conditions were carried out.The tunnel responses (transversal deformation and additional forces) at different transverse sections are presented.The maximum response of those was shown in the monitoring section (center of pile row section).Meanwhile, the torsion deformations are maximum as the 12 -30 m ( ≈ 1.5Dtunnel -4.5Dtunnel) away from the center of the pile row.For both short and long pile conditions, the influence zones of loaded pile row in a longitudinal direction are independent of the pile length and extended horizontal distance of 2Dtunnel away from the last pile within a row.
Keywords: Response analysis; Geotechnical Engineering and Underground Structures